The effects of endurance training on the relationships body composition plasma ghrelin and leptin levels - Behic Serpek; Sukran Arıkan (Türk Spor ve Egzersiz Dergisi)
The present research was conducted over 35 voluntary students studying at Collage of Physical Education and Sports of Selcuk University. The students were at 18-24 years age group and were composed of 18 women (10 experimental and 8 control) and 17 men (9 experimental and 8 control). A special diet program was not applied to experimental students. Experimental groups were subjected to 60 minutes cycling exercises in 4 days of the week for 8 weeks at 50-70% of previously determined heart rate. Control groups were prevented from any special sportive activities except for their practical courses. Ghrelin levels were measured by Enzyme Immuno Assay (EIA) and leptin levels were measured by ELISA method. Effects of gender on body weights, percent body fat (PBF) and maximal aerobic capacities (VO2max) of the men and women students measured at the beginning and end of the tests were found to be significant (P lt;0.001). Exercises significantly increased only VO2max levels of men and women experimental groups (P lt;0.001). Pre- and post-experimental leptin and ghrelin levels were also significantly affected by the gender (P lt;0.001), however, exercises did not significantly affect the levels of these hormones.  It was concluded that endurance trainings did not have significant effects on body weights, PBF and body mass index (BMI) of both men and women experimental groups, but significant increases were observed in VO2max levels  of entire experimental students with applied exercise programs and gender was found to be significant with regard to body weight, PBF and VO2max levels of the students. Additionally, leptin and ghrelin levels were not also significantly affected by the applied exercise program, but the effects of gender on leptin and ghrelin levels were found to be highly significant.